Composition and structure of riparian woodlands in three sub-watersheds of Tuttle Creek Watershed - Barahona Ochoa, Merilin Gisely (Kansas State University, 2014)
Spring Creek, Headwaters Robideux Creek, and Snipe Creek are sub-watersheds located within the Big Blue River Watershed, which drains to the Tuttle Creek Reservoir impoundment. This reservoir had a very high monetary investment since the beginning; unfortunately the lifespan for this marvel of engineering is declining rapidly due to high sedimentation rates. One of the programs for slowing the sedimentation process is the removal of highly erodible lands from agricultural production. This thesis work aimed to gather more knowledge on the natural riparian areas, to help the stakeholders of Kansas to improve their riparian woodland management decisions. The objective of the study was to characterize the structure and composition of natural riparian woodlands in three sub-watersheds of the Tuttle Creek Watershed. Data was collected using a representative sample design. Plot dimensions for mature tree data collection were 50ft by 30ft. For regeneration smaller, circular plots were used. Data analysis was completed with SAS 9.3. Results showed that trees per acre (TPA) differed significantly between Spring Creek and Snipe Creek, with Snipe Creek having the highest number of TPA. Quadratic mean diameter (QMD) also differed significantly in these two watersheds, with Spring Creek having the highest quadratic mean diameter. A different set of species was found in each watershed, with American elm (Ulmus americana) and hackberry (Celtis occidentalis) being found in high numbers in all areas. Regeneration data showed hackberry to be present in high numbers of both seedlings and saplings. Seedlings exhibited more species diversity than saplings. High economic value species were present in the natural riparian woodlands but in low numbers. Species of moderate economic value were predominant in terms of BA, TPA, and regeneration. Human impact on the riparian areas in the sub-watersheds was noticeable, both from livestock and forest management. Also invasive species were found in the riparian woodlands such as garlic mustard (Alliaria petiolata) and stinging nettles (Urtica diotica). Riparian areas have a great potential for improvement and management in the three sub-watersheds.
Keywords: Riparian woodlands; Water quality; Tuttle Creek; Kansas; Forestry (0478)